Implementing stereoscopic video processing on FPGA - Hjartarson, Ástvaldur; Nordmark, Klas (My University, 2015)
The purpose of this thesis is to investigate the viability of using FPGA acceleration in the processing of a stereoscopic video feed. This is done by comparing speed for a given processing resolution with a software implementation, as well as investigating power and area usage. The processing performed include greyscaling, remapping, resizing, Gaussian blur and Sobel filtering. Methods for disparity map calculations are also investigated. A system capable of processing video at 60 stereo frame pairs per second was developed.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science